Antisolvent based ultrasound-assisted batch and continuous flow precipitation of metformin hydrochloride particles - Pal, Sayan; Nikam, Arun V.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2021)
Small sized particles of the antidiabetic drug metformin hydrochloride (MET.HCl) were produced by antisolvent based precipitation using an ultrasound assisted inverted jet reactor (IJR). This novel approach was implemented as a small passive mixer in which intensified turbulent mixing of the solution and the antisolvent occurred under controlled conditions. The optimized conditions for antisolvent precipitation (ASP) were investigated by studying the effect of solute concentration, antisolvent to solvent ratio and antisolvent temperature in batch systems. The optimized batch precipitation conditions were successfully translated into continuous flow process for the ultrasound assisted inverted jet reactor. The ability of the proposed clogging free inverted jet reactor approach can provide a scaled up alternative pathway to micro and millifluidic devices for manufacturing of small sized API particles, such as, MET.HCl for the formulations and encapsulations on an industrial scale.
Keywords: Continuous antisolvent precipitation; Jet-reactor; Metformin; supersaturation; Ultrasound